EFFECT OF SELF EFFICACY, POSITIVE BELIEF AND SOCIAL SUPPORT ON ROLE ADAPTATION OF POST PARTUM MOTHER WITH POST-TRAUMA STRESS DISORDER (PTSD) IN KEDIRI DISTRICT - Reni Nurhidayah; Sri Poeranto; Asti Melani Astari (Journal of Nursing Science Update (JNSU), 2017)
Childbirth is a stressfull event, frequently labor can result PTSD in post partum period. The impact of post partum PTSD is a bonding issue between mother and baby that can affect the mother's ability to adapt to her new role. To Adapting with a new role mother requires an effective coping mechanism that is supported by an adequate coping source that includes self efficacy, positive belief and social support. The study describe the effect of self efficacy, positive belief and social support on adaptation of post partum mother role with PTSD. The study used cross sectional design. The sampling technique was purposive sampling and the numbers of samples were 92 respondents. The instruments for evaluate PTSD and coping was Modified PPQ, Barkin Index, PMP-SE, PPSS and PBRS. Pearson correlation test showed that all variables have p value <0,05, which means that all variables have effect on mother role adaptation. Linear Regression Test showed that self efficacy with R square 0.487 is the variable that most contribute to the mother role adaptation than the others. All variables have contribution, but self efficacy has the most significant influence on mother role adaptation. Therapeutic Activity Therapy in primary setting is needed to help pregnant women prepared adaptation